Christ is the question - Meeks, Wayne A. (2006)
The author argues that Jesus' identity is not a permanent historical artifact to be uncovered by careful technique but the outcome of transactions between him and those who knew/know him. Because the transactions are still going on we are still learning who Jesus is.
Answers and questions -- Does anybody know my Jesus? : between dogma and romanticism -- Memory and invention : the making of Jesus Christ -- A story to think with : from crucifixion to metaphor -- The Bible teaches--through a glass darkly -- Is Jesus the last word?
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- Person and offices